Catastrophe models and the expansion method: A review of issues and an application to the econometric modeling of economic growth. Issue 3 (1997) - Casetti, Emilio
Abstract : Many negative reactions to Catastrophe Theory have been triggered by overly simplistic applications unintended and unsuited for statistical-econometric estimation, inference, and testing. In this paper it is argued that stochastic catastrophe models constructed using the Expansion Method hold the most promise to widen the acceptance of Catastrophe Theory by analytically oriented scholars in the social sciences and elsewhere. The paper presents a typology of catastrophe models, and demonstrates the construction and estimation of an econometric expanded cusp catastrophe model of economic growth.